2015
DOI: 10.1007/s12035-015-9342-8
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Variants of the BH4 Biosynthesis Pathway Gene GCH1 and the Risk of Orofacial Clefts

Abstract: A deficiency of GTP cyclohydrolase, encoded by the GCH1 gene, results in two neurological diseases: hyperphenylalaninaemia type HPABH4B and DOPA-responsive dystonia. Genes involved in neurotransmitter metabolism and motor systems may contribute to palatogenesis. The purpose of the study was to analyse polymorphic variants of the GCH1 gene as risk factors for non-syndromic cleft lip with or without cleft palate (NSCL/P). Genotyping of nine polymorphisms was conducted in a group of 281 NSCL/P patients and 574 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A study conducted by Lupo and colleagues (16) suggested a link between haplotypes of GCH1 gene and ab- normal neural tube closure in the USA. In our previous study, we found a significant association between the GCH1 rs17128077, rs8004018 and rs17128050 variants with an in-creased risk for cleft lip with or without cleft palate (9). The correlation with single polymorphic variants was confirmed at the haplotype level (9).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…A study conducted by Lupo and colleagues (16) suggested a link between haplotypes of GCH1 gene and ab- normal neural tube closure in the USA. In our previous study, we found a significant association between the GCH1 rs17128077, rs8004018 and rs17128050 variants with an in-creased risk for cleft lip with or without cleft palate (9). The correlation with single polymorphic variants was confirmed at the haplotype level (9).…”
Section: Discussionmentioning
confidence: 71%
“…In our previous study, we found a significant association between the GCH1 rs17128077, rs8004018 and rs17128050 variants with an in-creased risk for cleft lip with or without cleft palate (9). The correlation with single polymorphic variants was confirmed at the haplotype level (9). The investigated variants of the GCH1 were not found to be involved in the pathogenesis of HS.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations